TAQNĪN AL-AHKĀM (Telaah Sejarah Legislasi Hukum Perdata Islam dalam Hukum Nasional Indonesia) - Miftahul Ulum Ismail; Moh. Mujibur Rohman; Mohsi Mohsi (Ulumuna: Jurnal Studi Keilsman, 2020)
In establishing law (istinbath al-hukm) Islam uses an approach to the al-Qur'an and al-Hadith, where both are references to all legal problems. Indonesia is a country with the largest majority of Muslims in the world. Not so, the existence of Indonesia as a law state that adheres to a democratic system requires the existence of Islamic legal legislation from living law to legal law. Where, Fiqh began to be formulated into constitution. Therefore, Indonesia, which is known as the trias politica government system (Judicative, Executive and Legislative), must also provide space for Muslims in the National Legislation Program (Prolegnas) to form Islamic law in Indonesia. This legislative process in Islam is known as Taqnīn Al-Ahkām (legal legislation).